Walking Biomechanics and Spine Loading in Patients With Symptomatic Lumbar Spinal Stenosis - Mousavi, Seyed Javad; Lynch, Andrew C.; Allaire, Brett T.; White, Andrew P.; Anderson, Dennis E. (Frontiers in Bioengineering and Biotechnology, 2021)
Symptomatic lumbar spinal stenosis is a leading cause of pain and mobility limitation in older adults. It is clinically believed that patients with lumbar spinal stenosis adopt flexed trunk posture, or bend forward and alter their gait pattern to improve tolerance for walking. However, biomechanical assessment of spine posture and motion during walking is broadly lacking in these patients. The purpose of this study was to evaluate lumbar spine and pelvis sagittal angles, and lumbar spine compressive loads in standing and walking, and to determine the effect of pain and neurogenic claudication symptoms in patients with symptomatic lumbar spinal stenosis. Seven participants with symptomatic lumbar spinal stenosis, aged 44 to 82, underwent a 3D opto-electronic motion analysis during standing and walking trials in asymptomatic and symptomatic states. Passive reflective marker clusters (4 markers each) were attached to participants at T1, L1, and S2 levels of the spine, with additional reflective markers at other spinal levels, as well as the head, pelvis, and extremities. Whole body motion data was collected during standing and walking trials in asymptomatic and symptomatic states. The results showed that spine was slightly flexed during walking, but this was not affected by symptoms. Pelvic tilt was not different when symptoms were present, but suggest a possible effect of more forward tilt in both standing (p = 0.052) and walking (p = 0.075). Lumbar spine loading during symptomatic walking was increased by an average of 7% over asymptomatic walking (p = 0.001). Our results did not show increased spine flexion (adopting a trunk flexed posture), and only indicate a trend for a small forward shift of the pelvis during both symptomatic walking or standing. This suggests that provocation of symptoms in these patients does not markedly affect their normal gait kinematics. The finding of increased spine loading with provocation of symptoms supports our hypothesis that spine loading plays a role in limiting walking function in patients with lumbar spinal stenosis, but additional work is needed to understand the biomechanical cause of this increase.